How Storytelling Enhanced Elementary Students’ English Proficiency - Mafulah, Siti; Panggala, Oka Bruno Asmara; Herawati, Siane (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
Teaching English to young learners requires creativity and engaging methods. Storytelling offers an alternative approach suitable for young students. This study aims to explore the English abilities of young learners through the use of storytelling. Data were collected through observations and interviews. Observations were conducted to examine students' activity in using English in the classroom, while interviews were carried out to strengthen the observational data. The participants were 26 students, with 10 selected for interviews to further validate their perceptions of storytelling activities. The findings indicate that storytelling has a positive influence on students' English abilities, particularly in speaking (including pronunciation and vocabulary). Interviews revealed that students found storytelling enjoyable, motivating, and helpful in learning English. These findings suggest that storytelling can serve as an effective alternative method for teaching English to young learners.